Morfometry of the crab-eating-fox skull Cerdocyon thous - Maximiano Neto, Antonio (2017)
ABSTRACT CHAPTER 2 The objectives of this study were to obtain measurements on skulls of Cerdocyon thous, establishing the standardization of craniometric values for this species and observe if the craniometric classification of domestic dogs and Chrysocyon brachyurus (wolves) is appropriate for C. thous. Eleven C. thous fox skulls were used, irrespective of age and sex. It was determined the location of nine craniometric points used in domestic dogs for C. thous. The points were reference to the 17 craniometric measures used for the calculation of six craniometric indexes. Craniometric indexes are 53.17 ± 2.54 mm cephalic, 2.33 ± 0.08 mm facial skull, 59.17 ± 3.57 mm neuroskull, 125.58 ± 6.63 mm facial, 37.52 ± 2.65 mm basal, and the foramen Magnum 54.47 ± 3.48 mm. According to the analyzed indexes C. thous is classified as mesaticefalic. ABSTRACT CHAPTER 3 Among the wild Canids the C. thous is what has the largest distribution in the national territory, from dense forests to open fields. Accidents with wild carnivores causing dental trauma are commom, as consequences of fights with other animals, accidents in bars and concrete protection of enclosures or even capture stress in routine exams in zoos. That way it is essential to use the preventive medicine and dentistry, to maintain the health and well-being of the animal in captivity. The present work brings anatomical landmarks and the infraorbitale foramen of the morphometric skull of C. thous, in order to assist anesthesiologists in procedures inherent to the anesthetic blockade infraorbitale nerve and its branches. Eight measurements were conducted in 11 skulls, in both antimeres, irrespective of sex and age. We use 28 correlations between the measures to make the statistical analysis. To the infraorbitale nerve blockage, indicates that the hypodermic needle is introduced into the oral vestibule, close to the side of the jaw bone in vertical direction between the third and fourth premolar teeth around 4.04mm to the right and 3.88 mm to the left until the edge of the ventral foramen infraorbitale.